Suitable for leak prevention and plugging of hard and brittle formations and cement slurry systems

By using modified rigid materials and comonomer saturated sodium chloride aqueous solution in hard and brittle formations, combined with external soft and internal rigid materials, the problem of sealing the low-strength and high-brittle leakage formations is solved, and effective clogging effect and material stability.

CN116333701BActive Publication Date: 2025-01-10CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310384932.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2025-01-10
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent leakage in low-strength and high-brittle leakage formations. Conventional leak-blocking materials cannot effectively seal them in hard and brittle formations, and it is easy to weaken the rock structure or lead to material waste.

Method used

The leak plugging agent prepared by reverse phase suspension polymerization of modified rigid materials and comonomer saturated sodium chloride aqueous solution is used to control the water absorption behavior of the material in cement slurry and utilize the change of sodium chloride concentration. Achieve leakage plugging effect of blocking pores.

Benefits of technology

The leakage plugging effect of hard and brittle formations is significantly improved, the cement slurry viscosity is avoided, and the effective sealing of the material and the stability of the rock structure is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116333701B_ABST
    Figure CN116333701B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of oil and gas well engineering cementing and oilfield chemistry, and specifically relates to a plugging agent and cement slurry system suitable for preventing and plugging hard and brittle formations. The plugging agent is obtained by suspension polymerization of a continuous phase and a dispersed opposite phase; the continuous phase contains a modified rigid material; the dispersed phase is a saturated sodium chloride aqueous solution containing a comonomer. The present invention adopts a saturated sodium chloride aqueous solution to dissolve the comonomer and then initiate polymerization. After drying, the water-absorbing material contains a large amount of sodium chloride. At the same time, the cement slurry slurry water also adopts a saturated sodium chloride aqueous solution, which can effectively control the plugging material from absorbing water in the cement slurry, and prevent the plugging material from absorbing a large amount of water in the cement slurry and causing the cement slurry viscosity to increase. In the hard and brittle leakage layer, the plugging material enters the formation with the cement slurry. After being diluted by the formation fluid, the sodium chloride concentration decreases, and the plugging material begins to absorb water and expand, thereby blocking the formation pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oil and gas well engineering cementing and oilfield chemistry, and in particular relates to a plugging agent and a cement slurry system suitable for preventing and plugging leakage in hard and brittle formations. Background Art

[0002] As the intensity of deep-water drilling in the ocean continues to increase, more and more complex situations are encountered. Due to the special sedimentary environment of deep water, the pressure of the overburden is low, and there are low-strength and high-brittle leakage strata in deep water, such as reef limestone strata. The basic characteristics of this type of strata are looseness, porosity, low strength and high brittleness. Its main component is coral sand (calcareous sand). The bearing capacity of calcareous sand is much smaller than that of quartz sand. The internal pores of calcareous sand particles determine that it is fundamentally different from quartz sand, and the particles are easily broken by external forces.

[0003] At present, each oil field solves the leakage problem of pores and microcracks by adding plugging materials to cement slurry. However, for low-strength and high-brittle leakage formations, conventional plugging materials cannot form effective plugging. For example: conventional rigid granular materials can not only not plug the leakage formation, but will weaken the rock structure, increase the connected pores, and the more plugging, the more leakage; flexible materials are a kind of material that will deform when squeezed, mainly gel materials, which can plug leakage channels of different shapes, but the skeleton support effect in the channel is weak, and it is very easy to be squeezed into the deep pores under the action of pressure difference, and it cannot form effective plugging, and it will also cause material waste. Therefore, this problem is improved by combining rigid materials and flexible materials. For example: Chinese patent document CN111218261A discloses a method for preparing an organic-inorganic composite material, which uses acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and acrylic acid as organic material parts, and nano calcium carbonate as inorganic material, and adopts solution polymerization to prepare the organic-inorganic composite material. However, the product prepared by the above method needs to be ground to obtain the required particle size, and the grinding process may cause the problem of inorganic calcium carbonate falling off; and the shape of the ground material is irregular particles, which will affect the fluidity of the cement slurry when added to the cement slurry, thereby affecting on-site construction.

[0004] CN113528101A proposes a plugging material that is flexible on the outside and rigid on the inside and a method for preparing the plugging material. Water-absorbing resin is coated on the surface of rigid particles to form a plugging agent that is flexible on the outside and rigid on the inside. However, the water-absorbing resin on the outer layer will absorb a large amount of water in the cement slurry, resulting in an increase in the viscosity of the cement slurry. Summary of the invention

[0005] In view of the characteristics of hard and brittle formations, the present invention proposes a plugging agent and a cement slurry system suitable for preventing and plugging leakage in hard and brittle formations.

[0006] The plugging agent for preventing and plugging hard and brittle formations of the present invention is obtained by suspension polymerization of a continuous phase and a dispersed opposite phase; the continuous phase contains a modified rigid material; and the dispersed phase is a saturated sodium chloride aqueous solution containing a copolymerized monomer.

[0007] The modified rigid material is modified silicon dioxide and / or modified quartz sand, which is modified by a silane coupling agent (γ-methacryloxypropyltrimethoxysilane (KH570); the comonomer is a mixture of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and N-vinyl pyrrolidone; in terms of mass ratio, acrylamide: 2-acrylamide-2-methylpropanesulfonic acid: N-vinyl pyrrolidone = (14-16): (3-2): (3-2). The mass ratio of the modified rigid material to the flexible material is 1: (10-25).

[0008] The preparation method of the plugging agent suitable for preventing and plugging leakage in hard and brittle formations comprises the following specific steps:

[0009] (1) Adding a dispersant and a modified rigid material into cyclohexane to prepare a continuous phase;

[0010] (2) dissolving the comonomer in a saturated sodium chloride aqueous solution to form a solution I, and then adding a cross-linking agent to prepare a dispersed phase;

[0011] (3) Add the dispersed phase dropwise into the continuous phase while stirring. When the temperature rises to 60°C~70°C, add the initiator to initiate the reaction. After the reaction is completed, filter and dry to obtain the final product.

[0012] In terms of mass ratio, n-hexane: saturated sodium chloride aqueous solution = 2:1.

[0013] In step (1), the amount of dispersant added is 4%-6% of the mass of cyclohexane. The dispersant is Span-80.

[0014] In step (1), the amount of modified rigid material added is 1-2.5% of the mass of cyclohexane.

[0015] In step (1), in solution I, the mass fraction of the comonomer is 44%.

[0016] In the present invention, the cross-linking agent is N,N-methylenebisacrylamide; the initiator is potassium persulfate-sodium bisulfite, and the mass ratio is 1:1.

[0017] The plugging agent suitable for preventing and plugging hard and brittle formations described in the present invention can be used to prepare a cementing slurry system suitable for preventing and plugging hard and brittle formations; the cement slurry system is composed of the following components: 100 parts of oil well cement, 4 parts of soft-outer-hard-inner plugging material, 4 parts of anti-salt fluid loss agent, 3 parts of anti-salt retarder, and 44 parts of slurry preparation water. The anti-salt fluid loss agent and the anti-salt retarder are mostly sulfonic acid / carboxylic acid copolymers commonly used in the art. The slurry preparation water is a saturated sodium chloride aqueous solution.

[0018] The present invention adopts saturated sodium chloride aqueous solution to dissolve the comonomer and then initiate polymerization. After drying, the water-absorbing material contains a large amount of sodium chloride. At the same time, the cement slurry slurry water also adopts saturated sodium chloride aqueous solution. This method can effectively control the water absorption of the plugging material in the cement slurry, prevent the plugging material from absorbing a large amount of water in the cement slurry and causing the cement slurry viscosity to increase. In the hard and brittle leakage layer, the plugging material enters the formation with the cement slurry, and after being diluted by the formation fluid, the sodium chloride concentration is reduced, and the plugging material begins to absorb water and expand, thereby blocking the formation pores. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Scanning electron microscope image of the soft-outer-hard-inner plugging material. DETAILED DESCRIPTION

[0020] Example 1

[0021] Modification method of rigid material quartz sand:

[0022] (1) First, pre-hydrolyze KH570 by mixing 4 g KH570, 75 g anhydrous ethanol, and 25 g distilled water in beaker A, adjusting the pH to 5 with dilute hydrochloric acid, and transferring the mixture to a three-necked flask. Stir vigorously at room temperature for 30 min to complete the pre-hydrolysis.

[0023] (2) Add 100 g of anhydrous ethanol and 20 g of quartz sand to beaker B, place it in an ultrasonic cleaner and shake it for 20 min, then transfer it to a three-necked flask;

[0024] (3) Nitrogen was introduced and the temperature was raised to 70°C. The reaction was carried out at a stirring speed of 350 r / min for 6 h. The reaction was stopped and the mixture was washed with anhydrous ethanol for 4 times after cooling. The mixture was filtered and dried to obtain modified quartz sand.

[0025] Example 2

[0026] The preparation method of gel microspheres without modified rigid materials comprises the following specific steps:

[0027] (1) Add 80 g of cyclohexane and 4 g of Span-80 to a three-necked flask equipped with a reflux condenser, a stirring blade and a nitrogen tube, and stir at high speed at 30°C for 20 min to obtain a continuous phase;

[0028] (2) Weigh 40 g of saturated sodium chloride aqueous solution in a beaker, add 14 g of acrylamide, 3 g of 2-acrylamido-2-methylpropanesulfonic acid, 3 g of N-vinyl pyrrolidone, and then add 0.1 g of N,N-methylenebisacrylamide, stir evenly, and prepare a dispersed phase;

[0029] (3) Take the prepared dispersed phase and add it dropwise to the continuous phase at a uniform rate while stirring. When the temperature rises to 70°C, add an appropriate amount of potassium persulfate-sodium bisulfite (1:1) mixed aqueous solution into the flask to initiate the reaction. After the reaction is completed, filter and dry at 70°C to obtain the final product.

[0030] Example 3

[0031] A method for preparing a plugging agent suitable for preventing and plugging leakage in hard and brittle formations, the specific steps are:

[0032] (1) Add 80 g of cyclohexane, 4 g of Span-80, and 0.8 g of modified sand into a three-necked flask equipped with a reflux condenser, a stirring blade, and a nitrogen tube, and stir at high speed at 30°C for 20 min to evenly disperse the quartz sand to obtain a continuous phase;

[0033] (2) Weigh 40 g of saturated sodium chloride aqueous solution in a beaker, add 14 g of acrylamide, 3 g of 2-acrylamido-2-methylpropanesulfonic acid, 3 g of N-vinyl pyrrolidone, and then add 0.1 g of N,N-methylenebisacrylamide, stir evenly, and prepare a dispersed phase;

[0034] (3) Take the prepared dispersed phase and add it dropwise to the continuous phase at a uniform rate while stirring. When the temperature rises to 70°C, add an appropriate amount of potassium persulfate-sodium bisulfite (1:1) mixed aqueous solution into the flask to initiate the reaction. After the reaction is completed, filter and dry at 70°C to obtain the final product.

[0035] Example 4

[0036] A method for preparing a plugging agent suitable for preventing and plugging leakage in hard and brittle formations, the specific steps are:

[0037] (1) Add 80 g of cyclohexane, 3.2 g of Span-80, and 1.2 g of modified sand into a three-necked flask equipped with a reflux condenser, a stirring blade, and a nitrogen tube, and stir at high speed at 30°C for 20 min to evenly disperse the quartz sand to obtain a continuous phase;

[0038] (2) Weigh 40 g of saturated sodium chloride aqueous solution in a beaker, add 15 g of acrylamide, 3 g of 2-acrylamido-2-methylpropanesulfonic acid, 3 g of N-vinyl pyrrolidone, and then add 0.1 g of N,N-methylenebisacrylamide, stir evenly, and prepare a dispersed phase;

[0039] (3) Take the prepared dispersed phase and add it dropwise to the continuous phase at a uniform rate while stirring. When the temperature rises to 60°C, add an appropriate amount of potassium persulfate-sodium bisulfite (1:1) mixed aqueous solution into the flask to initiate the reaction. After the reaction is completed, filter and dry at 70°C to obtain the final product.

[0040] Example 5

[0041] A method for preparing a plugging agent suitable for preventing and plugging leakage in hard and brittle formations, the specific steps are:

[0042] (1) Add 80 g of cyclohexane, 4.8 g of Span-80, and 1.6 g of modified sand into a three-necked flask equipped with a reflux condenser, a stirring blade, and a nitrogen tube, and stir at high speed at 30°C for 20 min to evenly disperse the quartz sand to obtain a continuous phase;

[0043] (2) Weigh 40 g of saturated sodium chloride aqueous solution in a beaker, add 16 g of acrylamide, 3 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of N-vinyl pyrrolidone, and then add 0.1 g of N,N-methylenebisacrylamide, stir evenly, and prepare a dispersed phase;

[0044] (3) Take the prepared dispersed phase and add it dropwise to the continuous phase at a uniform rate while stirring. When the temperature rises to 65°C, add an appropriate amount of potassium persulfate-sodium bisulfite (1:1) mixed aqueous solution into the flask to initiate the reaction. After the reaction is completed, filter and dry at 70°C to obtain the final product.

[0045] Example 6

[0046] A method for preparing a plugging agent suitable for preventing and plugging leakage in hard and brittle formations, the specific steps are:

[0047] (1) Add 80 g of cyclohexane, 4 g of Span-80, and 2 g of modified sand into a three-necked flask equipped with a reflux condenser, a stirring blade, and a nitrogen tube, and stir at high speed at 30°C for 20 min to evenly disperse the quartz sand to obtain a continuous phase;

[0048] (2) Weigh 40 g of saturated sodium chloride aqueous solution in a beaker, add 14 g of acrylamide, 2 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of N-vinyl pyrrolidone, and then add 0.1 g of N,N-methylenebisacrylamide, stir evenly, and prepare a dispersed phase;

[0049] (3) Take the prepared dispersed phase and add it dropwise to the continuous phase at a uniform rate while stirring. When the temperature rises to 70°C, add an appropriate amount of potassium persulfate-sodium bisulfite (1:1) mixed aqueous solution into the flask to initiate the reaction. After the reaction is completed, filter and dry at 70°C to obtain the final product.

[0050] The materials in Examples 1 to 6 were added to cement slurry to test the plugging effect on the core (simulating hard and brittle formation) prepared from coral sand. The specific process is as follows:

[0051] (1) Check whether the designed coral sandstone core meets the experimental requirements;

[0052] (2) Check the connectivity and sealing of the leak plugging instrument to see if it meets the required pressure of the experiment;

[0053] (3) Prepare base slurry and prepare 400 mL of cement slurry;

[0054] (4) Weigh the plugging material, add it to the base slurry and stir at a low speed;

[0055] (5) Place a graduated cylinder at the outlet, add the test slurry into the cylinder, and record the volume and time of slurry outflow;

[0056] (6) If there is no leakage or the leakage stops after a small amount of slurry is lost, connect the nitrogen device to increase the pressure to a maximum of 7 MPa. After each pressurization to the set value, close the valve and hold the pressure for 5 minutes. Open the valve to observe the slurry leakage and the minimum pressure at which plugging may occur. Record it. If plugging is successful, maintain the pressure for 10 minutes and record the final leakage.

[0057] Coral sand, with a mesh size of about 20 (the core pore size formed is about 200μm, the permeability is distributed between 2000-16445 mD, and the strength is maintained between 1.89-9.42 MPa, which is consistent with the characteristics of hard and brittle formations).

[0058] Cement slurry base slurry formula: Jiahua "G" grade cement 100 parts + saturated sodium chloride aqueous solution 44 parts + anti-salt fluid loss agent 4 parts + anti-salt retarder 3 parts. The amount of plugging agent is 4 parts.

[0059] Table 1 Sand bed plugging data of each embodiment

[0060] .

[0061] From the analysis of the data in Table 1, we can see that:

[0062] (1) Without the addition of plugging materials, the base slurry will not have a plugging effect and will all leak out at 0.5 MPa.

[0063] (2) When 4 wt % of modified quartz sand (150-200 mesh, prepared in Example 1) was added to the base slurry, there was no leakage at normal pressure, but all the slurry leaked out at 0.5 MPa. The reason may be that the quartz sand particles are hard. When the pressure increases, the quartz sand particles are squeezed into the pores, causing the pores in the core to expand, the permeability to increase, and the slurry loss to increase.

[0064] (3) Adding 4 wt% of gel microspheres (prepared in Example 2) without modified rigid material into the base slurry had a certain plugging effect. However, when the pressure increased to 2 MPa, the slurry was completely lost. The main reason was that a single gel microsphere did not have a skeleton support function. When the pressure increased, too many gel microspheres would be squeezed into the deep pores or even penetrate the core, so that the material could not remain in the pores and could not form a bridging effect, resulting in the complete loss of the slurry.

[0065] (4) After the modified rigid material is wrapped with elastic resin, the plugging effect on hard and brittle formations is significantly improved.

[0066] (5) Too little modified rigid material is added, resulting in the existence of excess flexible material in the form of single gel microspheres, resulting in poor plugging effect. When too much is added, the surface wrapping material of the modified rigid material becomes thinner, the flexibility becomes worse, and even naked rigid material exists, which will cause certain leakage when the pressure increases.

Claims

1. A cementing slurry system suitable for preventing and plugging leaks in hard and brittle formations, characterized in that: The invention is composed of the following components: 100 parts of oil well cement, 4 parts of plugging agent, 4 parts of anti-salt fluid loss agent, 3 parts of anti-salt retarder, and 44 parts of slurry preparation water, wherein the slurry preparation water is a saturated sodium chloride aqueous solution; The plugging agent is obtained by suspension polymerization of a continuous phase and a dispersed phase; the continuous phase contains a modified rigid material; the dispersed phase is a saturated sodium chloride aqueous solution containing a comonomer; the modified rigid material is modified silicon dioxide and / or modified quartz sand; the comonomer is a mixture of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and N-vinyl pyrrolidone; in terms of mass ratio, acrylamide:2-acrylamido-2-methylpropanesulfonic acid:N-vinyl pyrrolidone=(14-16):(3-2):(3-2); The specific preparation steps of the plugging agent are: (1) Adding a dispersant and a modified rigid material into cyclohexane to prepare a continuous phase; (2) dissolving the comonomer in a saturated sodium chloride aqueous solution to form a solution I, and then adding a cross-linking agent to prepare a dispersed phase; (3) Add the dispersed phase dropwise to the continuous phase while stirring. When the temperature rises to 60°C to 70°C, add the initiator dropwise to initiate the reaction. After the reaction is completed, filter and dry to obtain a plugging agent. The cross-linking agent is N,N-methylenebisacrylamide; The initiator is potassium persulfate-sodium bisulfite, and the mass ratio is potassium sulfate:sodium bisulfite=1:1; In terms of mass ratio, cyclohexane: saturated sodium chloride aqueous solution = 2:1; In step (1), the amount of modified rigid material added is 1-2.5% of the mass of cyclohexane; In step (2), the mass fraction of the comonomer in solution I is 30%-35%.

2. The cementing slurry system suitable for leak prevention and plugging in hard and brittle formations according to claim 1 is characterized in that: In step (1), the amount of dispersant added is 4%-6% of the mass of cyclohexane.

Citation Information

Patent Citations

  • Organic / inorganic composite gel plugging agent with rigid interior and flexible exterior, and preparation method thereof

    CN111218261A

  • Lost circulation material with soft outside and rigid inside and preparation method thereof

    CN113528101A